Thymic Hassall's corpuscles in Nandanam chicken - light and electronmicroscopic perspective (Gallus domesticus). Issue 1 (December 2015) - Kannan, Thandavan; Ramesh, Geetha; Ushakumary, S.; Dhinakarraj, Gopalan; Vairamuthu, Subbiah
Abstract The present study was aimed to study the light and electron microscopic studies of thymic Hassall's corpuscles was done in various age groups of Nandanam Chicken ranging from day-old to forty weeks. Hassall's corpuscles are special, unique structures present in thymic medulla and also in the cortex of all the age groups of Nandanam chicken (from hatch to forty weeks) in the present study. Size of the Hassall's corpuscles in the medulla is larger than the ones present in the cortical region of thymus. The Hassall's corpuscles are made up of structureless eosinophilic mass surrounded by concentrically arranged reticuloepithelial cells. Under electron microscope, the Hassall's corpuscles were composed of reticuloepithelial cells interconnected by many desmosomes. The epithelial cells had abundance of cytoplasmic fibrils and desmosomes with few mitochondria and ribosomes. The nucleus was oval or round which was slightly indented. The centre of the Hassall's corpuscles was appeared either solid or cystic. The cystic corpuscles had cell debris within the cyst lumen.